2017
DOI: 10.1371/journal.pone.0182614
|View full text |Cite
|
Sign up to set email alerts
|

Risk of long-term infection-related death in clinical osteoporotic vertebral fractures: A hospital-based analysis

Abstract: BackgroundOsteoporotic vertebral fractures adversely impact quality of life and also increase the risk of infection and mortality. Alendronate treatment increases bone mass and reduces the risk of fractures in patients with osteoporosis by suppressing bone resorption. We investigated the relationship between alendronate treatment and infection-related death in patients with osteoporotic vertebral fractures.MethodsWe retrospectively reviewed patients with osteoporosis and vertebral fractures from January 2001 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 24 publications
0
15
0
Order By: Relevance
“…Of these twelve patients, 5 patients (41.67%) died during their in-hospital stay (4 proximal femoral fractures, 1 hip prosthesis traumatic dislocation). Patients died on average, 8.2 days [4][5][6][7][8][9][10][11][12][13][14] after hospitalization. The remaining seven patients were discharged after a prolonged hospital stay.…”
Section: Our Experiencementioning
confidence: 99%
“…Of these twelve patients, 5 patients (41.67%) died during their in-hospital stay (4 proximal femoral fractures, 1 hip prosthesis traumatic dislocation). Patients died on average, 8.2 days [4][5][6][7][8][9][10][11][12][13][14] after hospitalization. The remaining seven patients were discharged after a prolonged hospital stay.…”
Section: Our Experiencementioning
confidence: 99%
“…COVID-19, which started to be a big problem for the whole world after March 2020, began to change the surgical trends. COVID-19's highly contagious feature, transmission by droplet, contact and air, and being infectious even without specific symptoms during the incubation period and susceptibility to pulmonary infection in patients especially with lower-limb fracture are major concerns in the treatment of fracture patients [5]. The simplest rule to prevent contamination is to avoid exposure to the virus.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that there can be a transmission from patients to surgeons, as well as from surgeons to patients. COVID-19 infection may also develop in some patients after surgical treatment because orthopedic surgeries tend to produce more aerosols and droplets due to use of high-speed operative devices [5].…”
Section: Introductionmentioning
confidence: 99%
“…In turn, mobility is inextricably linked to functional improvement. 25 Furthermore, pain may impair respiratory function which is of particular importance given Chen et al 6 emphasized that chest infection is the leading cause of death in OVFs. This review uncovered moderate-quality evidence that both FEV1 and vital capacity is likely to be improved by wearing a spinal orthosis, further advocating for spinal orthosis use.…”
Section: Discussionmentioning
confidence: 99%